Finansowanie wspólnej polityki rolnej z budżetu Unii Europejskiej - Biernat-Jarka, Agnieszka (The Common Agricultural Policy Financing from the European Union's Budget, 2005)
The 2005 budget was adopted by the Parliament on 16 December 2004. It totals 106 300 million euro in appropriations for payments. This represents an increase of 4,4% in payment appropriations in relation to the 2004 budget. Payment appropriations are at 49 115 million euro, which represants an increase of 11,6% on the 2004 budget. The increases can be explained by the second stage of the phasing - in direct aids for the new member states and by the effects of the reform of the Common Agricultural Policy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 60-64